Peran Teknologi Digital dalam Pengembangan Pembelajaran Kristen di Era Digital - Jonatan, Jonatan; Waruwu, Anwar Three Millenium (Institut Teknologi Pendidikan Indonesia, 2023)
This article focuses on the role of digital technology in the development of Christian education in the digital era. The article presents the research background by explaining the importance of adapting Christian religious education to technological advancements and the demands of the time. The objective of this study is to answer questions related to the role of digital technology in the development of Christian education. The research methodology employed in this study is a qualitative approach using a literature review. Through literature analysis, the research findings conclude that by wisely utilizing digital technology, Christian education can become more dynamic, interactive, and relevant in the digital era. Digital technology enables more engaging learning experiences through the use of instructional videos, multimedia-based digital resources, and interactive simulations. However, challenges such as the negative influence on Christian values and the morality of students need to be addressed. In this regard, the responsibility of Christian educators is crucial in building students' character and ensuring the appropriate use of digital technology in accordance with Christian principles.